Implementation of The Speech Recognition System Using a real time web Server Based - Aditya, Moch. Vicky; Setiawan, Aries Boedi; rabi, Abdur (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
a Speech Recognition is a system used to recognize word commands from human voices and then translated them into data that can be understood by a computer. The advantages of Speech Recognition include speed and ease of use. Merdeka Malang is a private university founded on January 29, 1964. The University of Merdeka Malang still doesn’t have a strategy in recommending new students based on historical data calculations in choosing faculties. and majors. In calculating the history, if you use a manual system, they will be constrained by the time and accuracy of the data, causing the data to be less valid.Therefore, there is a need for a system that can exchange data in real-time so that the data displayed is always up to date without manual data updating. This process is useful for monitoring and accelerating the process of calculating student interest data, which can later be recommended to future new students. Moreover, The speech technique used is using speech recognition which is used for processing speech data on smartphones while sending data using the XAMPP web server which is used to exchange data from smartphones to servers.